th The concept of Doubt in Ancient Iraq - الاعرجي, أ. م. د. حسين سيد نور جلال (lark, 2020)
The concept of Doubt in Ancient IraqThe idea of ​​research is summed up in the concept of doubt, the concept that recorded the moment of questioning and searching for the importance of life and existence for a person, and his rejection of what was found by the ideas and beliefs used by the Ancient Iraqi man, the system of values, morals, social customs, religious beliefs and the place of man in the gods and the other person.The research was divided according to the importance of the concept and its emergence, as well as the chronology of each example, which demonstrated the Doubt of the Iraqis with those ideas and beliefs. Most of the sources of doubt were reflected in the environment and political and social conflicts, and they appeared clearly in literary literature since the third millennium BC, but flourished at the end of the second millennium and the beginning of the first millennium BC, according to most of the texts discovered.The researcher reached important results, the first of which is that the Ancient Iraqi mentality is a Moving and renewed mindset that rejected the values ​​that people are returning, whether religious or social, to reach a conclusion that the revolution on concepts must continue to advance the human being seeking renewal.
Keywords: )Doubt / ancient Iraq / ancient literature / glory of the Lord of wisdom(